The impact of Blended Learning and Team Teaching in tertiary pre-service music education classes - Jenkins, Louise; Crawford, Renee (Journal of University Teaching and Learning Practice, 2016)
The nature of tertiary teaching is metamorphosing at a pace consistent with the expectations and requirements of an innovative society. This is due to more accessible advanced technology, the targeted use of online learning, student expectations for a flexible learning environment and the pressures of faculty budgets. As a result, more innovative approaches to teaching and learning are required. In response, a project is investigating the implementation of a Blended Learning process within tertiary pre-service music education classes, underpinned by Team Teaching strategies. This paper will report on some of the findings of the project’s first two years of research.